Tax law system in the context of digitalization: problems and prospects - O. I. Lyutova (Правоприменение)
The purpose of the article is to develop a criterion for structuring the branch of tax law relevant for the period of digitalization.The methodology of the study includes an analysis of regulatory acts of tax legislation regulating the legal regulation of digital transformation of taxation.The main results and the scope of their application. Due to the lack of a single criterion for the formation of the structure of tax law (in different years, the tax system or the system of tax legislation was considered as such), obstacles are created in the unambiguity of understanding the system and types of tax law institutions. This leads to a number of practical problems related to the “alignment” of new tax law norms that appeared in the digital era into the “classical” tax legal relationship.Conclusions. The criterion on the basis of which the modern legislator, as well as representatives of the tax and legal doctrine, divides tax law into institutions is a controversial issue of the relevant branch of science. Such uncertainty does not give an unambiguous understanding of the legal nature of new tax law institutions, for example, the institute of a single tax payment. At the present stage, it would be logical to use the category of “tax obligation” as a kind of link in the system of tax law, which is predetermined by its fundamental role in tax and legal regulation.